Can the Innovations of the Fourth Technological Revolution Occur within Public Administration Systems? - Schweinheim, Guillermo (Revista del CLAD Reforma y Democracia, 2020)
Theoretical approaches and applied research on the relationship between technological changes and innovations and public administration are usually characterized by a type of work program that explains the changes in public administration based on the technological transformations and innovations taking place in “society”. However, comparative experience, and also that of Latin America, shows how in multiple occasions the technological changes and innovations produced within public administration systems have impacted on social processes, re-enrolling economic and social actors, including large business actors, in these innovations and producing changes with intensive use of ICT which transformed social associations at the national, continental and global levels. The article explores the cases of changes in financial administration, procurement and contracting and public revenue systems produced in Latin America, using the science and technology studies of the Network Actor Theory. It addresses its implications in relation to the transformations known as the fourth industrial revolution, the different ways of dealing with the processes of change, innovation, adaptation or modernization of public administrations, and the way in which innovation in State administrations, especially in the fourth technological revolution, can lead to broader social transformations.
Keywords: Administrative Innovation; Technological Development; Financial Management; Financial Systems; Government Purchasing; Public Contracts; Public Income; Public Sector; Latin America